Ekstraksi fenol dari daun sirsak (annona murcata l): sokletasi dan destilasi - Fitrianny, Eka; Adhani, Lisa; Nuraliyah, Andi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Soursop, with the Latin name Annona muricata L, has become one of the herbal medicine materials under extensive development. One of the challenges faced in utilizing extracts from soursop leaves currently is the inefficiency of the solvents used. Methods: This study aims to determine the phenol content present in soursop leaves. The independent variable used is the process of drying soursop leaves before the soxhlet extraction process. The purpose of this process is to increase the phenol content in the concentrated soursop leaf extract after the soxhlet extraction process. Thus, this research involves two processes, namely the soxhlet extraction and distillation processes. Findings: The phenol content obtained from the FT-IR test is approximately 80-85% with an intensity at 3347.82 cm-1. Furthermore, the distillation process is carried out to obtain a distillate that will be tested using GC-MS instrument. The results of the GC-MS test show a value of approximately 1.723 with an area of 78.04. Conclusion: The longer the immersion of soursop leaves and the higher the concentration of the solvent used, the better the results tend to be. Identification of the effects of using different solvents with the same functional groups becomes important in further research.